Webinar: bicara @APB50 series 2 (with MoU & MoA partners) - UiTM Shah Alam, Akademi Pengajian Bahasa (Academy of Language Studies, 2022)
On 10th November 2022, APB50 organised a Webinar: Bicara @APB50 Series from 9 am to 12 pm. The webinar entitled "Language in the Global Perspective: Maximising Potential for Academics and Students' was streamed live on APB YouTube channel and APB Facebook page. The webinar proudly featured speakers from APB's MoU and MoA partners such as Asian China Education and Culture (Mr. Yang Cheng Cheng), Jeonbuk National University (Prof. Shim Jae-Woo), Universidad Catolica Del Maule (Mr. Jorge Burgos Munoz), and University of Wisconsin-Eau Claire (Dr.Kaishan Kong).